Chemical Co-Precipitation Method to Prepare Magnetite Nanoparticles - Mohamed, Hasan Daw A.; Khalifa, Mohamed Ammar M.; Ashtewi, Mahmud Ashtewi S. (جامعة الزيتونة - كلية الآداب والعلوم - ترهونة, 2016)
Iron oxide (Fe304) nanoparticles were prepared using co-precipitation method. This facile and conventional approach involved co-precipitation of aqueous solutions of Fe3+/Fe2+ salts by the addition of a base. The product material was then characterized using FTIR spectroscopy and powder X-ray diffraction, which confirmed the iron oxide formed to be the Fe3O4 crystal phase. Atomic force microscopy (AFM) studies revealed that the resulting Fe3O4 nanoparticles have spherical morphologies with mean size of 23 nm, which was in good agreement with the estimated Fe3O4 crystallite size that was determined from powder XRD data using Scherrer's equation. Statistical analysis of the average diameter showed moderately wide size distributions (2-31 nm) with modal value identified as 23 nm.
في هذه الدراس تم تحضير الجسيمات النانومترية من أكسيد الحديد (Fe3O4) باستخدام طريقة الترسيب المصاحب، هذه الطريقة تتضمن ترسيب أكسيد الحديد من المحلول المائي الذي يحتوي على أيونات الحديد الثنائي والثلاثي وذلك بإضافة مادة قاعدية. وتمت دراسة الناتج المتحصل عليه باستخدام طيف الأشعة تحت الحمراء (FTIR) وحيود الأشعة السينية (XRD) وذلك لمعرفة تركيبه الكيميائي. وأثبتت نتائج هذه التحاليل أن الناتج المتحصل عليه هو أكسيد الحديد في شكل المغناتيت (Fe3O4)، في حين بينت نتائج مجهر القوى الذرية (AFM) المستخدم للتعرف على الشكل الهندسي وقياس حجم الجسيمات، أن الجسيمات النانومترية من المغناتيت لها شكل كروي متجانس بمتوسط نصف قطر يساوي 23 نانومتر، وهذا يتوافق مع حجم الجسيمات المحسوبة من نتائج حيود الأشعة السينية (XRD) باستخدام معادلة شيرر. بالإضافة إلى ذلك بينت نتائج التحليل الإحصائي أن متوسط حجم الجسيمات يقع في المدى ما بين 5 – 30 نانومتر.
Keywords: هطول الأمطار -- الجسيمات النانومترية